Probiotic Protects Kidneys Exposed to Microcystin-LR - Hu, Yolanda; Sun, Irene; Tang, Eric; Ryan, William; Shrestha, Upasana; Gautam, Jyotshana; Lad, Apurva; Huntley, Jason F.; Haller, Steven; Kennedy, David (Translation: The University of Toledo Journal of Medical Sciences, 2024)
Cyanobacterial Harmful Algal Blooms (CyanoHABs) occur when colonies of photosynthetic bacteria called cyanobacteria grow out of control, usually in warm, nutrient-rich, slow-moving waters. They are becoming increasingly prevalent around the world and release harmful toxins called cyanotoxins into bodies of water, which negatively affect human and ecological health. One such cyanotoxin is microcystin, with microcystin-leucine arginine (MC-LR) being the most widespread. Exposure to MC-LR inhibits serine and threonine protein phosphatase 1 and 2A in humans, causing a myriad of health problems. Fortunately, certain naturally occurring bacteria may be able to degrade MC-LR and reverse its effects. Mice were separated into five experimental groups based on three types of pre-treatments (control drinking water/vehicle, probiotic-supplemented drinking water, and heat-inactivated probiotic-supplemented drinking water) as well as two types of exposures (microcystin-LR and water/vehicle). RNA was extracted from kidneys for sequencing because MC-LR exacerbates kidney disease. Gene expression data were analyzed with 3 Pod Reports, an R package that produces a three-part report consisting of Gene Set Enrichment Analysis (GSEA), EnrichR, and integrative LINCS (iLINCS). MC-LR exposure was associated with upregulated cellular respiration and metabolism pathways and downregulated transcription pathways. Probiotic pre-treatment combined with MC-LR exposure was associated with upregulated lipoprotein particle pathways and downregulated respiration and ribosome pathways. Overall, the probiotic mixture corrected the transcriptional profile resulting from MC-LR exposure. Future high yield pathways that could be targeted for therapeutic benefit include VEGFR inhibitors and increased expression of renal kidney indicator genes such as EGFR.